The Role of Education Supervisors is to Improve the Professionalism of Teachers in Blended Learning in RA Al Mubarak for the 2019/2020 Academic Year - Neny Mulyati (Journal of Social Research, 2023)
This research reveals the Role of Education Supervisors in Improve Teacher Professionalism in Blended Learning. The formulation of the problem in this study is how is the role of education supervisors to improve teacher professionalism in blended learning at RA Al Mubarak. The purpose of this study is to reveal the influence of the Role of Education Supervisors to Improve Teacher Professionalism in Blended Learning at RA Al Mubarak In the implementation of transformational leadership in teachers, it was found that a positive influence on the creation of teacher work professionalism in teaching and learning activities, this was marked by a significant increase in each cycle, cycle I by 56% and cycle II by 100%. This shows the successful role of education supervisors in efforts to Improve Teacher Professionalism in Blended Learning at RA Al Mubarak.